Life Cycle Cost Analysis of Ashore Marine Engine Room - Long Lyu; Long Huang; Jing Yu (Advances in Civil Engineering)
This paper aims to present a method for comparing decision options for the ashore marine engine room. Based on the life cycle cost system, the life cycle stages are divided into design, acquisition, installation, operation, maintenance, and scrapping. A model of the life cycle cost of ashore marine engine room considering the time value of money was developed, and a calculation method for sensitivity analysis was developed. Regarding the actual case, the life cycle cost of the two options was estimated, the sensitivity of the cost of the two options was analyzed, and control recommendations were made. The results show that Option 2, with the highest initial investment, is the optimal solution, attributed to using an advanced two-stroke diesel engine with reduced operation and maintenance costs. This will be useful for reference by maritime academies.